The Effect of Adolescent Knowledge about Menstruation on Personal Hygiene Behavior during Menstruation in Environment III Silandit Village - Juliana Lubis; Eva Yusnita Nasution; Wiwi Wardani Tanjung (Institute of Computer Science (IOCS), 2022)
Reproductive Health What is most important is complete physical, mental and social well-being, not only because you are free from disease or disability, in all aspects related to the reproductive system, its functions and processes, including being male or female. The research was conducted to determine the effect of adolescent knowledge about menstruation on personal hygiene behavior when menstruation occurs in environment III, Silandit village. This research is analytic with a cross sectional design, with a population and sample of 33 young women who are in environment III Silandit village. This study shows the results that there is an influence of adolescent knowledge about menstruation on personal hygiene behavior when menstruation occurs in the environment III Silandit village with a value of p = 0.005 <p = 0.05. The conclusion in this study is to be able to provide counseling to adolescents related to reproductive health in adolescents, especially young women by related agencies or related parties.